2018
DOI: 10.1051/matecconf/201817205005
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal & Risk Assessment during Threshing of Rice-grains

Abstract: Abstract. In the present study 25 farmers of five villages of South Odisha in India were considered to assess their musculoskeletal disorders (MSD) during threshing of crops. A "Standardized Nordic Questionnaire" was prepared to collect MSD data considering harvesting characteristics, socio-demographic characteristics, economical characteristics about the requirements, and work setting characteristics, by using a five point rating scale i.e. (1 = Very less, 2 =Less, 3 = Nil, 4 = Strong, 5 = Very Strong) for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…More than 50% of working postures were found to be at high risk, necessitating further assessments and changes. This result agrees with studies identi ied earlier that farm workers were at risk of MSDs due to awkward postures [13,22,25,26,29]. Harmful postures which were found while performing tasks attributed to musculoskeletal injury exposure required corrective measures.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…More than 50% of working postures were found to be at high risk, necessitating further assessments and changes. This result agrees with studies identi ied earlier that farm workers were at risk of MSDs due to awkward postures [13,22,25,26,29]. Harmful postures which were found while performing tasks attributed to musculoskeletal injury exposure required corrective measures.…”
Section: Resultssupporting
confidence: 92%
“…The overexertion, differential fatigue and cumulative load theories explain the precipitation of musculoskeletal injuries [23]. Studies have shown that inappropriate working posture must be considered in order to categorize the level of physical exertion and musculoskeletal symptoms [4,5,22,24,25,26].…”
Section: B Musculoskeletal Disorders Related To Working Pos-mentioning
confidence: 99%
See 1 more Smart Citation